Pharmacokinetics and Pharmacodynamics of Canagliflozin, a Sodium Glucose Co‐Transporter 2 Inhibitor, in Subjects With Type 2 Diabetes Mellitus. (14th May 2013) - Devineni, Damayanthi; Curtin, Christopher R.; Polidori, David; Gutierrez, Maria J.; Murphy, Joseph; Rusch, Sarah; Rothenberg, Paul L.
Abstract This study characterized single‐ and multiple‐dose pharmacokinetics of canagliflozin and its O‐glucuronide metabolites (M5 and M7) and pharmacodynamics (renal threshold for glucose [RTG], urinary glucose excretion [UGE0–24h], and 24‐hour mean plasma glucose [MPG0–24h]) of canagliflozin in subjects with type 2 diabetes. Thirty‐six randomized subjects received canagliflozin 50, 100, or 300 mg/day or placebo for 7 days. On Days 1 and 7, area under the plasma concentration‐time curve and maximum observed plasma concentration (Cmax) for canagliflozin and its metabolites increased dose‐dependently. Half‐life and time at which Cmax was observed were dose‐independent. Systemic molar M5 exposure was half that of canagliflozin; M7 exposure was similar to canagliflozin. Steady‐state plasma canagliflozin concentrations were reached by Day 4 in all active treatment groups. Pharmacodynamic effects were dose‐ and exposure‐dependent. All canagliflozin doses decreased RTG, increased UGE0–24h, and reduced MPG0–24h versus placebo on Days 1 and 7. On Day 7, placebo‐subtracted least‐squares mean decreases in MPG0–24h ranged from 42–57 mg/dL with canagliflozin treatment. Adverse events (AEs) were balanced between treatments; no treatment‐related serious AEs, AE‐related discontinuations, or clinically meaningful adverse changes in routine safety evaluations occurred. The observed pharmacokinetic/pharmacodynamic profile of canagliflozin in subjects with type 2 diabetes supports a once‐daily dosing regimen.